(untitled) (History Journal «Jerónimo Zurita», 2025)
Doña María del Pilar Silva y Palafox (1766-1835) was the second wife of the 10th Count of Aranda. Belonging by birth to the Dukes of Híjar lineage, she was a young woman educated in the Enlightenment ideals who get married following a careful strategy of noble families’ connection. The countess joined her husband as feminine companion for the ambassador in Paris and was an active member of the Madrid aristocracy when she returned to the Spanish court. This paper will seek to cover the biography of the lady during her time as consort and widow countess of Aranda to analyse her figure as a powerful woman of her time and representative of the noble female model during the second half of the Spanish 18th century.